Platform Economics and Marketplace Dominance: Analysis of Marketplace Business Models in Global Competition - Oktaviani Oktaviani (PT. Anagata Sembagi Education, 2025)
The expansion of the platform economy has fundamentally transformed global market competition by introducing new forms of dominance driven by data control, algorithms, and network effects. Digital platforms no longer operate merely as transaction intermediaries but function as market infrastructures that regulate access, value distribution, and economic behavior across industries. This study aims to examine how platform business models construct market dominance and how such dominance reshapes global competitive structures. The research adopts a qualitative approach through a systematic literature review and critical conceptual analysis of leading academic publications. Data were collected from high-impact international journals and analyzed using thematic synthesis and comparative interpretation. The findings reveal that platform dominance is produced through the interaction of subsidy wars, network effects, ecosystem integration, data ownership, and global expansion strategies. These mechanisms generate high entry barriers, intensify economic dependency on platforms, and weaken conventional competition mechanisms. The study concludes that the platform economy demands a new competition policy paradigm and digital market governance framework to ensure that technological innovation remains aligned with competitive fairness and long-term economic sustainability.